2007
DOI: 10.1111/j.1748-5827.2006.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Vedaprofen therapy in cats with upper respiratory tract infection or following ovariohysterectomy

Abstract: Vedaprofen produced a clinically relevant reduction in body temperature and a more rapid return to normality in cats with upper respiratory tract disease. Vedaprofen treatment also resulted in more rapid recovery, presumably through the relief of pain and inflammation, in cats that had undergone soft tissue surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…, 2007). However, recent studies have shown the use of vedaprofen to treat cats with upper respiratory tract disease at the recommended dose period is highly effective and does not cause observable adverse effects (Lopez et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2007). However, recent studies have shown the use of vedaprofen to treat cats with upper respiratory tract disease at the recommended dose period is highly effective and does not cause observable adverse effects (Lopez et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the usage, safety and efficacy of new NSAIDs have already been reported in dogs, there have been a number of studies that describe adverse effects when using these drugs in cats (Lascelles et al, 2007). However, recent studies have shown the use of vedaprofen to treat cats with upper respiratory tract disease at the recommended dose period is highly effective and does not cause observable adverse effects (Lopez et al, 2007). Tolfenamic acid has also been used to suppress inflammation in respiratory tract infections, relieve postoperative pain after ovariohysterectomy, and control fever in cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Few studies have looked at prolonged postoperative analgesic treatment. 12,13 Vedaprofen is a preferential cyclo-oxygenase-2 nonsteroidal anti-inflammatory drug (NSAID) inhibitor in dogs. 14 It is an effective anti-inflammatory and analgesic in this species for treating musculoskeletal pain.…”
mentioning
confidence: 99%
“…Η μετεγχειρητική χορήγηση της, μετά από επέμβαση ωοθηκυστερεκτομής σε δόση 0,5 mg/kg μία φορά ημερησίως για τρεις συνεχόμενες ημέρες, εί χε ικανοποιητικό αναλγητικό αποτέλεσμα χωρίς την εμφάνιση παρενεργειών, συμφωνά με τους ιδιοκτήτες των ζώων, οι οποίοι ήλεγχαν την ποιότητα της προκα λούμενης αναλγησίας (Lopez et al 2007). …”
Section: μη στεροειδή αντιφλεγμονώδη φάρμακαunclassified